BONDRES DANGDANG KETEKUNG SEBAGAI MEDIA KOMUNIKASI PENDIDIKAN - Eka Putri, Niluh Wiwik (Institut Hindu Dharma Denpasar, 2021)
One of the Balih-balihan arts is bondres. Bondres is often performed in ritual activities in Bali. Bondres is used as a communication medium that can educate the public with unique packaging such as displaying funny characters, as well as fresh humor. The implementation of ceremonial traditions and arts for Balinese Hindus is inherent. Bondres Dangdang Ketekung still exists in the midst of the development of communication technology, it can be proven by the fact that they often fill events in various activities in Buleleng Regency. With still active Dangdang Ketekung, it indicates if the community is entertained by his jokes. In addition, Dangdang Ketekung also uses social media such as Facebook, Instagram and YouTube to be better known by the wider community, especially the younger generation. The communication of education implemented in the Dangdang Ketekung bondres mask performance is expected to be able to make an important contribution in understanding and practicing the interactions and actions of all individuals involved. In their performances, they understand communication models such as dialogic, persuasive and educative. So that the teachings of education can be conveyed to the public. One of them is about the teachings of Tri Kaya Parisudha, Tri Kita Karana, and topics that are currently trand.